1994
DOI: 10.3109/01485019408987788
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Semen Characteristics and Regulatory Factors in Human Semen with Bacterial Infection

Abstract: Semen samples (n = 40) obtained from males attending an infertility clinic were subjected to bacteriological culture and categorized as bacteriologically negative (group I) and bacteriologically positive (group II) depending on the culture positivity. Semen samples from both groups were simultaneously analyzed for routine parameters such as volume, count, motility, viability, morphology, pH, and hypoosmotic swelling. Seminal plasma was assayed for levels of prolactin (PRL), prolactin-suppressing factor (PSF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
2
4
1
1
Order By: Relevance
“…Bacteria such as E. coli have been confirmed to cause infertility by reducing sperm vitality (2,29). However, here we observed distinct effects of the various E. coli isolates.…”
Section: Discussioncontrasting
confidence: 62%
“…Bacteria such as E. coli have been confirmed to cause infertility by reducing sperm vitality (2,29). However, here we observed distinct effects of the various E. coli isolates.…”
Section: Discussioncontrasting
confidence: 62%
“…Although seminal infection has been associated with poor sperm quality (Gopalkrishnan et al ., ; Sanocka‐Maciejewska et al ., ; Moretti et al ., ), the UPEC studied here were heterogeneous in their effects on sperm motility and did not affect vitality or ΔΨm. Our results show that not all UPEC decrease the sperm motility, vitality or ΔΨm.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors have speculated that the infectious process in the male genitourinary tract may limit fertility through testis damage and affect the biologic function of mature gametes (1,2). Most have suggested that the invasion of microorganisms into the male reproductive system could be detrimental to semen quality, sperm motility, and sperm viability and subsequently to sperm biologic function (3,4).…”
mentioning
confidence: 98%